Seasonal and geographic variation of atmospheric ozone, derived from Nimbus 3 - Prabhakara, C.; Goddard Space Flight Center.; United States. National Aeronautics and Space Administration. (Washington, D.C. : National Aeronautics and Space Administration, 1971)
Nimbus 3 infrared interferometer spectrometer (IRIS)measurements of the intensities in the 9.6-pn region are used to derive the ozone content in the atmosphere between latitudes SOON and 80's. The global distribution of total ozone was mapped for eight days in April and eight days in July 1969. These global maps of total ozone are compared with the upper-air oonstant pressure maps to emphasize the meteorological significance of the ozone variations in time and space. The total ozone has a minimum value of about 0.25 cm STP in the equatorial regions and increases markedly toward both poles. In the Arctic region, the total ozone in the spring time is well above 0.5 cm STP, while in summer it is about 0.4 cm STP. An eight-day mean global map of total ozone for April 1969 clearly reveals the presence of climatological large-scale ozone systems in the atmosphere. Another such map, for July 1969, shows that these systems have weakened considerably in the northern hemisphere. Seasonal variability in the total ozone over the southern hemisphere is much less pronounced. Close association between the total-ozone systems and tropospheric weather systems is shown for several cases. From this study, it is concluded that the atmospheric ozone, remotely sensed by satellites, can be used as a meteorological parameter to diagnose the present state of the atmosphere, and, thereby, aid weather prediction. "N71-32791." Prepared at Goddard Space Flight Center. Includes bibliographical references (p. 47-49). Nimbus 3 infrared interferometer spectrometer (IRIS)measurements of the intensities in the 9.6-pn region are used to derive the ozone content in the atmosphere between latitudes SOON and 80's. The global distribution of total ozone was mapped for eight days in April and eight days in July 1969. These global maps of total ozone are compared with the upper-air oonstant pressure maps to emphasize the meteorological significance of the ozone variations in time and space. The total ozone has a minimum value of about 0.25 cm STP in the equatorial regions and increases markedly toward both poles. In the Arctic region, the total ozone in the spring time is well above 0.5 cm STP, while in summer it is about 0.4 cm STP. An eight-day mean global map of total ozone for April 1969 clearly reveals the presence of climatological large-scale ozone systems in the atmosphere. Another such map, for July 1969, shows that these systems have weakened considerably in the northern hemisphere. Seasonal variability in the total ozone over the southern hemisphere is much less pronounced. Close association between the total-ozone systems and tropospheric weather systems is shown for several cases. From this study, it is concluded that the atmospheric ozone, remotely sensed by satellites, can be used as a meteorological parameter to diagnose the present state of the atmosphere, and, thereby, aid weather prediction. Mode of access: Internet.